Effect and UtilIzation of Crude oil on Some of Fungi Isolated From Soil - Shafiq, Sh. A.; Mizil, S. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study was conducted  to reveal the effect of crude oil  on some  fungal species  isolation from soil in order to evaluate the role of these fungi   in environmental  balance of soil . The results showed a variation in numbers and  percentage of  the fungal  isolates  Aspergillus fumigatus dominated over all   isolates with  a frequency of  (32.47) . In  respect  of  the effect of  different  concentrations of the crude oil,  low concentrations (0.05, 0.1) %  showed no    effect  on radial growth ( mean colony diameter) of the isolated fungi grown   on solid media , whereas other concentrations (5.10)% showed gradual toxic effect   on  these  fungi .  The  fungus  Aspergillus   fumigatus   reveal  higher  sensitivity   against  all  concentrations of the  crude oil  compared  to  others   species , The results  showed  also variation  of  these  fungi in  utilization of  the    crude oil on solid mineral  media used  as  a sole  carbon  and  energy source    with  the  different    concentrations of the crude oil , exposing time and  kind    of species.